2013
DOI: 10.1590/s0100-204x2013000200014
|View full text |Cite
|
Sign up to set email alerts
|

Expressão do mRNA de genes mitocondriais e desempenho produtivo de codornas alimentadas com glicerol

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito de dietas com glicerol no desempenho produtivo de codornas japonesas de corte e na expressão do mRNA de genes mitocondriais da proteína adenina nucleotídeo translocase (ANT) e da proteína desacopladora (UCP), envolvidas no metabolismo energético e na resposta ao estresse oxidativo. As codornas foram alimentadas com dietas contendo 0, 8 e 12% de glicerol, em substituição parcial ao milho. Aos 28 dias de idade, o RNA total foi extraído de amostras do músculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…This ingredient has been attributed the characteristic of improving the texture (PASQUETTI et al, 2014) and palatability (SILVA et al, 2013) of feeds, which are aspects responsible for increased feed intake. However, some studies have reported interference of some substances contained in crude glycerin that may lead to limitations to intake, such as the sodium content (GUERRA et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…This ingredient has been attributed the characteristic of improving the texture (PASQUETTI et al, 2014) and palatability (SILVA et al, 2013) of feeds, which are aspects responsible for increased feed intake. However, some studies have reported interference of some substances contained in crude glycerin that may lead to limitations to intake, such as the sodium content (GUERRA et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…A utilização de subprodutos na ração de animais, pode reduzir o custo de produção, e podendo também ocorrer um aumento na rentabilidade 2 . O glicerol, um subproduto do biodiesel, sempre que financeiramente rentável, pode ser administrado à ração como substituto energético do milho 3 .…”
Section: Introductionunclassified